Languages of sentiment : cultural constructions of emotional substrates - Palmer, Gary B., 1942-; Occhi, Debra J. (Advances in consciousness research, 1999)
Working from Radcliffe-Brown's landmark concept of social sentiments, anthropologists and linguists examine pragmatic and cognitive dimensions of emotion-language in several societies. Introductory and concluding chapters devote special attention to emotional consciousness. Chapters cover language primordialism in Tamil (Harold Schiffman), the erasure of lamentation in Bangla in favor of referential language praxis (James Wilce), women's discourse in Java that creates dignity by reframing the pain of humiliation (Laine Berman), speech styles signalling intimacy and remoteness in Japanese (Cynt.